Selection of a suitable photosynthetically active microalgae strain for the co-cultivation with mammalian cells - Dani, Sophie; Windisch, Johannes; Valencia Guerrero, Xally Montserrat; Bernhardt, Anne; Gelinsky, Michael; Krujatz, Felix; Lode, Anja (Frontiers in Bioengineering and Biotechnology, 2022)
Preventing hypoxic zones in 3D bioprinted mammalian cell-laden constructs using an internal oxygen supply could enable a more successful cultivation both in vitro and in vivo. In this study, the suitability of green microalgae as photosynthetic oxygen generators within bioprinted constructs was evaluated by defining and investigating important parameters for a successful co-culture. First, we assessed the impact of light–necessary for photosynthesis–on two non-light adapted mammalian cell types and defined red-light illumination and a temperature of 37°C as essential factors in a co-culture. The four thermotolerant microalgae strains Chlorella sorokiniana, Coelastrella oocystiformis, Coelastrella striolata, and Scenedesmus sp. were cultured both in suspension culture and 3D bioprinted constructs to assess viability and photosynthetic activity under these defined co-culture conditions. Scenedesmus sp. proved to be performing best under red light and 37°C as well as immobilized in a bioprinted hydrogel based on alginate. Moreover, the presence of the antibiotic ampicillin and the organic carbon-source glucose, both required for mammalian cell cultures, had no impact on bioprinted Scenedesmus sp. cultures regarding growth, viability, and photosynthetic activity. This study is the first to investigate the influence of mammalian cell requirements on the metabolism and photosynthetic ability of different microalgal strains. In a co-culture, the strain Scenedesmus sp. could provide a stable oxygenation that ensures the functionality of the mammalian cells.